Social representations of homolesbiantransphobies from the perspective of youths: the school context in action - Guilherme Franco Miranda; Márcia Amaral Corrêa Ughini Villarroel (Universidade Federal do Oeste da Bahia, 2020)
The purpose of this article is to analyze how social representations of homolesbiantransphobies in the school. At school, a homophobia and prejudices associated with it - as a set of beliefs, attitudes and behaviors associated with attributes attributed by the LGBTQI people - are expressed through verbal aggressions and/or violence student subjects who resist adapting to heteronormativity. The methodology was studied in a case of application of an instrument called Scale of Prejudice against Gender Sexual Diversity (EPDSG) - in a Public State School of Microregion 8 in Porto Alegre/RS -, this scale was selected to measure or prejudice against both gender regarding gender identity and transsexuality. The analysis of the results conceives as social representations as a process socially constructed by the subjects in their daily interactions, while acting in reality, showing an exclusion and marginalization of individuals who do not "fit" with these stereotypes.